1997
DOI: 10.1001/archpsyc.1997.01830130031006
|View full text |Cite
|
Sign up to set email alerts
|

A Linkage Study of Bipolar Illness

Abstract: Our results imply that a BP susceptibility gene exists near the centromere of chromosome 18. Confirmation of this finding (by independent investigators studying different pedigrees) has been published, suggesting that a valid BP disease linkage may have been discovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 45 publications
4
74
0
Order By: Relevance
“…Interestingly, positive findings were obtained after subdividing the families according to the gender of the disease-transmitting parent. Our linkage data support the modest evidence for linkage with markers on 18p11.2 originally reported by Berrettini et al 2,20 In accordance with the results of Stine et al 3 and Gershon et al 4 we found the highest LOD scores in the subset of paternal families. Moreover, our multipoint LOD score peaked at the same loci (D18S37, D18S453, D18S40; Figure 1) where Gershon et al 4 and Stine et al 3 found their highest LOD scores on 18p11.2.…”
Section: Affected-sib-pair Analysissupporting
confidence: 93%
“…Interestingly, positive findings were obtained after subdividing the families according to the gender of the disease-transmitting parent. Our linkage data support the modest evidence for linkage with markers on 18p11.2 originally reported by Berrettini et al 2,20 In accordance with the results of Stine et al 3 and Gershon et al 4 we found the highest LOD scores in the subset of paternal families. Moreover, our multipoint LOD score peaked at the same loci (D18S37, D18S453, D18S40; Figure 1) where Gershon et al 4 and Stine et al 3 found their highest LOD scores on 18p11.2.…”
Section: Affected-sib-pair Analysissupporting
confidence: 93%
“…Several regions on chromosome 18 have been implied [15][16][17][18][19][20][21][22][23] and reviewed by Potash and Depaulo Jr. 73 We have previously reported a lod score of 1.83 at D18S67 in family 4. 41 We did not find much support for this region with non-parametric analyses.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25] Low positive lod scores less than 1 have been reported by Sherrington et al 18 23 reported a lod score of 0.76 at 0.11 recombination fraction for D4S394 in one of their two Costa Rican families and of 1.06 at 0.07 recombination fraction at nearby marker D4S171 in the other Costa Rican family. As part of the NIMH genome scan, Detera-Wadleigh et al 26 did not find evidence of increased allele sharing at or near D4S394.…”
mentioning
confidence: 85%